2021
DOI: 10.1016/j.annepidem.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Material hardship, perceived stress, and health in early adulthood

Abstract: Objective We examined the associations between material hardship and health outcomes in early adulthood, and the extent to which these associations are mediated by perceived stress. Methods We used Wave I & IV of the National Longitudinal Study of Adolescent Health (Add Health), a nationally representative survey of young adults aged 18 to 34 years old ( N =13,313). Multivariate logistic regression and decomposition methods were used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Risk for the onset of internalizing mental health disorders, such as depression and anxiety ( Rapee et al, 2019 ), as well as substance use, including alcohol and cannabis ( Vega et al, 2002 ), is heightened during these formative years. As adolescents transition into early adulthood and assume greater responsibilities and obligations, it is common to experience additional stressors such as financial strain related to the insecurity of the labour market and economy, which can further contribute to poor health ( Huang et al, 2021 ; Institute of Medicine and National Research Council, 2014 ; Wood et al, 2018 ). Indeed, under the current context of the pandemic, young workers have experienced the largest declines in employment ( Gould and Kassa, 2020 ; Statistics Canada, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk for the onset of internalizing mental health disorders, such as depression and anxiety ( Rapee et al, 2019 ), as well as substance use, including alcohol and cannabis ( Vega et al, 2002 ), is heightened during these formative years. As adolescents transition into early adulthood and assume greater responsibilities and obligations, it is common to experience additional stressors such as financial strain related to the insecurity of the labour market and economy, which can further contribute to poor health ( Huang et al, 2021 ; Institute of Medicine and National Research Council, 2014 ; Wood et al, 2018 ). Indeed, under the current context of the pandemic, young workers have experienced the largest declines in employment ( Gould and Kassa, 2020 ; Statistics Canada, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Young people are generally defined as those aged late teens to 24 [ 1 ]. They usually experience major transitions to adulthood in terms of education, employment and social identity that are likely to engender uncertainty about their future [ 2 , 3 , 4 ]. Yet, independent living, marriage and parenthood have increasingly been delayed among young adults in the face of the neoliberal labor market, and hence, the age threshold for the sociological notion of young people has been extended to the early 30s [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While private rental is the most common tenure type in the early stage of independent living, it has increasingly been challenging for young people to access adequate and affordable housing due to the constantly rising housing prices [ 6 , 12 , 13 , 14 , 15 , 16 ]. A growing body of research has reported on delayed homeownership [ 17 ], increased house sharing [ 18 ], frustrated housing prospects [ 19 ] and material hardship [ 2 ] among young people today. Previous research focusing on children, older persons and low-income families found that an inadequate housing environment, housing cost burden, being a renter and insecure tenancy are associated with poor mental health [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we cannot rule out the possibility that the associations may be in the other direction—for example, poor SRH could increase stress, which then lowers social support. Although a majority of longitudinal studies find exposure to stress results in worsened health over time ( Huang et al, 2021 ; Moskowitz et al, 2013 ), research has also shown that poor health could itself be a major stressor, preceding more experiences of stress and distress ( Compas et al, 2012 ; Currie, 2009 ). Some studies also report that people who experience high levels of stress and distress have lessened social support as a result ( Platt et al, 2016 ; Thompson and Goodvin., 2016 ).…”
Section: Discussionmentioning
confidence: 99%